Thymine and Thymidine Uptake by Haemophilus influenzae and the Labeling of Deoxyribonucleic Acid - Carmody, Janice M. (1970)
The influence of ribo- and deoxyribonucleosides and ribo- and deoxyribonucleotides on the uptake of radiolabeled thymidine and thymine by Haemophilus influenzae during growth was investigated. A nucleoside-degrading enzyme similar to that reported in Escherichia coli was found to break down thymidine unless other nucleosides were present to divert its action. The presence of other nucleosides permitted a nearly quantitative uptake of even low levels of thymidine. This quantitative uptake of thymidine in the presence of an excess of other nucleosides suggests that the uptake mechanism for thymidine is specific in this organism. Under optimal conditions, as much as 50% of the deoxyribonucleic acid (DNA) thymine was derived from exogenous thymidine. Thymine was not taken up by H. influenzae but, in the presence of purine deoxynucleosides, labeled thymine entered the cells, presumably as thymidine. Ribonucleosides or ribonucleotides inhibited thymine conversion to thymidine, but, as noted above, they were degraded by a cellular enzyme. Thus, unless the ribonucleoside level was excessively high, a cell level of growth was reached at which the inhibiting ribonucleoside was broken down and labeled thymine appeared in the cells at an increasing rate. Twenty-five per cent of the DNA thymine of this organism was labeled with exogenous thymine. The information noted above serves as the basis for isotopically labeling the DNA.